2016
DOI: 10.1002/jbm.b.33809
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo study of commercial calcium phosphate cement HydroSet™

Abstract: The commercial calcium phosphate cement, HydroSet™, was investigated in vitro, studying phase formation, compressive strength and setting time, followed by an ovine in vivo study to measure osseointegration, bone apposition and bone-to-graft contact. The X-ray diffraction and P Magic Angle Spinning Nuclear Magnetic Resonance (MAS NMR) results showed the initial formation of octacalcium phosphate and hydroxyapatite at one hour. Over 7 days the octacalcium phosphate transformed to apatite, which was the only cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…To identify HAP in the nanocomposites, 31 P MAS nuclear magnetic resonance (NMR) spectra of the HAP nanocomposites synthesized via different ethanol/water ratios were performed and are included in Figure S2, Supporting Information. The results showed that the chemical shift of 31 P in the nanocomposites is in line with that of the HAP reported in the literature, [49] indicating that HAP was successfully synthesized in the matrix PTFE despite a low concentration. The IR spectrum of the in situfabricated PTFE nanocomposite presented a stretching mode of physiosorbed water at 3705 cm À1 , which is an indication of an increase in hydrophilicity in comparison with the matrix PTFE and suggested the presence of the HAP in situ filled.…”
Section: Structural Properties Of Hydroxyapatite Nanowires and Their ...supporting
confidence: 87%
“…To identify HAP in the nanocomposites, 31 P MAS nuclear magnetic resonance (NMR) spectra of the HAP nanocomposites synthesized via different ethanol/water ratios were performed and are included in Figure S2, Supporting Information. The results showed that the chemical shift of 31 P in the nanocomposites is in line with that of the HAP reported in the literature, [49] indicating that HAP was successfully synthesized in the matrix PTFE despite a low concentration. The IR spectrum of the in situfabricated PTFE nanocomposite presented a stretching mode of physiosorbed water at 3705 cm À1 , which is an indication of an increase in hydrophilicity in comparison with the matrix PTFE and suggested the presence of the HAP in situ filled.…”
Section: Structural Properties Of Hydroxyapatite Nanowires and Their ...supporting
confidence: 87%
“…Hence, PO 4 3– and Ca 2+ ions combine together with more difficulty, and calcium phosphate formation is partially prevented. This also explains the formation of a phosphorous-rich apatite compound, as evident from chemical composition analyses (Ca/P ∼0.7), and which has been reported to be helpful in promoting in vivo osseointegration. On the other hand, the negatively charged ZnO@GO surface is due to the intrinsic abundance of hydroxyl groups of GO and further promotes absorption of Ca 2+ ions from SBF solution. PO 4 3– are then attracted, and finally calcium phosphate compounds are formed.…”
Section: Resultsmentioning
confidence: 86%
“…It has been reported by Kent et al in vitro and in vivo measurements of commercial calcium phosphate cement is considerably stronger in vivo compared to in vitro, the cause of this attributed to bone formation within the cement pores and a high degree of osseointegration [131]. Chen et al, 2013 proved that when hUCMSCs and hBMSCs were seeded onto a CPC scaffold.…”
Section: In-vitro and In-vivo Studies Of Calcium Phosphate Cement (Cpmentioning
confidence: 94%